Didactic unit aimed towards educators for teaching english to students in 5th and 6th grades of the multigrade school of El Calvario, Bugaba 2011 - Ortega, Berta (David, Panamá : UDELAS, 2011)
This project is attempting to show some different and creative ways that teachers can use to teach students using didacaatic guides ar El Calvario Multigrade School.
GENERAL INDEX Presentation page Table of contenx English guides index Acknowledgement Dedication Introduction CHAPTER I Reference frame of the project CHAPTER II DESCRIPTION OF THE PROPOSAL 2.1. Description of the proposal 2.1.2. Project action areas 2.2. Lines of action of the project 2.2.1. Specific objectives 2.3. Activities 2.4.1. Description of activities 2.4.2. Methodology to be implemented for execution of activities 2.4.3. Instrument or guides to be used 2.5. Schedule of activities 2.6. Organization chart 2.6.1. Budgets 2.7. Human resources 2.8. Material resources 2.9. Evaluations 2.9.1. Evaluation guides 2.9.2. Teacher questionnarie Recommendations Conclusion Bibliographics
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- PROYECTO COMUNITARIO DE LICENCIATURA -- TEACHING; FACULTAD DE EDUCACIÓN SOCIAL; LICENCIATURA DOCENCIA EN INGLÉS; MULTIGRADE SCHOOL OF EL CALVARIO, BUGABA - CHIRIQUÍ